The Microbiota and It’s Correlation With Metabolites in the Gut of Mice With Nonalcoholic Fatty Liver Disease - Gu, Congwei; Zhou, Zihan; Yu, Zehui; He, Manli; He, Lvqin; Luo, Zhengzhong; Xiao, Wudian; Yang, Qian; Zhao, Fangfang; Li, Weiyao; Shen, Liuhong; Han, Jianhong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
In recent years, nonalcoholic fatty liver disease (NAFLD) has become the most common liver disease in the world. As an important model animal, the characteristics of gut microbiota alteration in mice with NAFLD have been studied, but the changes in metabolite abundance in NAFLD mice and how the gut microbiota affects these intestinal metabolites remain unclear. In this experiment, a mouse model for NAFLD was established by a high-fat diet. The use of 16S rDNA technology showed that while there were no significant changes in the alpha diversity in the cecum of NAFLD mice, the beta diversity changed significantly. The abundance of Blautia, Unidentified-Lachnospiraceae, Romboutsia, Faecalibaculum, Ileibacterium increased significantly in NAFLD mice, while Allobaculum and Enterorhabdus decreased significantly. 167 significantly different metabolites were selected, including amino acids, lipids, bile acids and nucleotide metabolites. The metabolic pathways of amino acids, SFAs and bile acids were significantly enhanced, while the metabolic pathways of PUFAs, vitamins and nucleotides were significantly inhibited. Through correlation and MIMOSA2 analysis, it is suggested that gut microbiota does not affect the changes of lipids and bile acids, but can reduce thiamine, pyridoxine, and promote L-phenylalanine and tyramine production. The finding of this study will help us to better understand the relationship between gut microbiota and metabolites in NAFLD.